Determinants of entrepreneurial intentions of private university students in Thailand - Nithima Yuenyong; Tanpat Kraiwanit; Ekaphot Congkrarian (International Journal of Evaluation and Research in Education (IJERE), 2026)
The growing interest in student entrepreneurship, research has yet to comprehensively examine both internal and external determinants of startup intentions among private university undergraduates in Thailand, a context shaped by rapid digital transformation and national innovation priorities. This study investigates the factors predicting entrepreneurial intentions among 400 undergraduate students at private universities in Pathum Thani, Thailand. Using a quantitative research design, data were collected via a validated structured questionnaire and analyzed through descriptive statistics and stepwise multiple regression. Five factors significantly predicted startup entrepreneurial intention: financial resources, entrepreneurial skills, prior experience, economic conditions, and technological factors, collectively explaining 60.3% of the variance. Financial resources and entrepreneurial skills emerged as the strongest predictors, while political-legal, socio-cultural, and environmental factors were not significant predictors. The study concludes that entrepreneurial intention is shaped by the interplay between individual competencies and contextual enablers. These findings call for universities to strengthen entrepreneurship education across all faculties and for policymakers to improve students' access to financial resources and startup support mechanisms.